Mauritius : Background Papers and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1996)
This Background Paper and Statistical Annex examines selected issues pertaining to the Mauritian economy, which are all related to the question of how Mauritius will be able in the future to sustain its export-led development and diversify its economy. The paper discusses the impact of the Uruguay Round agreement on the Mauritian economy. The paper also utilizes available data to assess Mauritius's external competitiveness, which is a major issue as regards the sustainability of high export growth.